Design of a Document Management System Application Using the Web-Based Rapid Application Development Method for Monitoring Perbal at Provincial Personnel Agencies in the Special Capital Region of Jakarta. - Putra, Rahmadika Roma; Yasin, Verdi; Zulhalim, Zulhalim; Yulianto, Akmal Budi (Jurnal Teknologi Informatika dan Komputer, 2025)
Implementation of the activity reporting system for DKI Jakarta DPRD members is a system to facilitate the reporting of activities of DKI Jakarta DPRD members. The DKI Jakarta DPRD member activity reporting system has been widely used in companies with various technologies and systems. The author raised the problem with the DKI Jakarta DPRD Secretariat. There is no special program for storing data and making reports at the DKI Jakarta DPRD Secretariat. This activity is very important, increases efficiency, and determines its performance in terms of cost savings. Previously, data processing was carried out manually using Microsoft Excel and Word, by designing a computerized system using PHP and MySql applications, data on the activities of DKI Jakarta DPRD members had been stored in a database to simplify the process of daily activities. This research uses data collection methods by means of observation, interviews and literature study, namely by making direct observations on the objects under study and requesting the necessary data, as well as interviews or questions and answers with sources to complete the data and obtain the necessary information.The system designed is an information system for the activities of DKI Jakarta DPRD members which was created using PHP and MySQL. This system was created to be able to manage data on the activities of DKI Jakarta DPRD members and reports. The information system designed is expected to minimize the shortcomings of the system currently used so that work activities are more effective, efficient and controlled.